Usage of the foreign websites on foreign language practical classes for development of students’ communicative competence - Irina A. Pushkareva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to considering the usefullness of authentic materials when teaching a foreign language in order to form the communicative competence of students. The author analyzes the concept of authenticity, highlighting its types, states and characteristics, as well as features of the use of authentic materials in the educational process. Classifying foreign official websites of law-enforcement bodies as authentic materials, the author considers them as one of their effective means of forming communicative competence in the absence of a natural linguistic environment. The author developed and methodically substantiated a system of working with authentic materials in the form of foreign official websites of law-enforcement bodies, which was tested in a practical lesson in a foreign language at the Kuzbass Institute of the Federal Penitentiary Service of Russia. The analysis of the experimental lesson allowed the author to come to conclusions about the feasibility and effectiveness of organizing work with authentic materials on the basis of a methodically developed task to form the communicative competence of students, expand their socio-cultural and professional knowledge and motivate them to study a foreign language.